COLLABORATIVE GOVERNANCE DALAM PENGENDALIAN PENCEMARAN LINGKUNGAN OLEH AKTIVITAS INDUSTRI PADA DAERAH ALIRAN SUNGAI (DAS) SIAK DI KOTA PEKANBARU - Handoko, Tito; Syofian, .; Tinov, M.Y Tiyas (Magister Administrasi Publik FISIP Universitas Mulawarman, 2018)
Environmental problems cannot be denied that there are industrial activities along the Siak watershed that ignore the principle of environmental ethics (sustainability, proportionality and responsibility) so that the impact on the quality of the environment in the Siak watershed is reduced. The purpose of this study is to see the government's commitment to supervise industrial activities that have an impact on environmental pollution along the Siak watershed (DAS) which covers the area of Pekanbaru and Siak. Research Methods through a qualitative approach by means of FGDs and Interviews to Industrial Stakeholders in the Siak watershed. This is because the institutional system of the program has not been able to manage social interaction among the various parties involved. As a result, starting from planning to program management has not been carried out based on environmental governance needs. Therefore, an institutional system is needed that is able to manage social interaction among various parties in minimizing environmental pollution by industrial activities along the Siak watershed. Based on these conditions, this paper produced a model for institutional strengthening through a collaborative governance approach to minimize environmental pollution in the Siak watershed.Keyword : Collaborative Governance, sustainable, proportional and environmental responsibility